Lifestyle intervention for type 2 diabetes patients - trial protocol of The Copenhagen Type 2 Diabetes Rehabilitation Project - Borg Eva; Perrild Hans; Frølich Anne; Vadstrup Eva S; Røder Michael (BMC, 2009)
Abstract Background Current guidelines recommend education, physical activity and changes in diet for type 2 diabetes patients, yet the composition and organization of non-pharmacological care are still controversial. Therefore, it is very important that programmes aiming to improve non-pharmacological treatment of type 2 diabetes are developed and evaluated. The Copenhagen Type 2 Diabetes Rehabilitation Project aims to evaluate the effectiveness of a new group-based lifestyle rehabilitation programme in a Health Care Centre in primary care. Methods/Design The group-based diabetes rehabilitation programme consists of empowerment-based education, supervised exercise and dietary intervention. The effectiveness of this multi-disciplinary intervention is compared with conventional individual counselling in a Diabetes Outpatient Clinic and evaluated in a prospective and randomized controlled trial. During the recruitment period of 18 months 180 type 2 diabetes patients will be randomized to the intervention group and the control group. Effects on glycaemic control, quality of life, self-rated diabetes symptoms, body composition, blood pressure, lipids, insulin resistance, beta-cell function and physical fitness will be examined after 6, 12 and 24 months. Discussion The Copenhagen Type 2 Diabetes Rehabilitation Project evaluates a multi-disciplinary non-pharmacological intervention programme in a primary care setting and provides important information about how to organize non-pharmacological care for type 2 diabetes patients. Trail Registration ClinicalTrials.gov registration number: NCT00284609.